Modular Multi-Parallel Rectifiers (MMR) with controlled DC link current - Zare, Firuz (2016)
© 2016 IEEE and EPE Association. This paper presents a new front end Modular Multi-Parallel Rectifiers (MMR) topology for three-phase systems with active DC link current controllers. Conventional three-phase diode rectifiers generate significant line current harmonics which affect power quality of distribution networks. Several passive and active harmonic mitigation techniques have been utilized to reduce line current harmonics. The proposed topology is suitable for high power application which can reduce line current harmonics emissions significantly. Analysis and simulations have been carried out to verify the proposed topology.